Berberine as a Natural Modifier of Gut Microbiota to Promote Metabolic Status in Animal Studies and Clinical Trials: A Systematic Review - Mohammad Sadegh Adel-Mehraban; Zahra Aghabeiglooei; Rasha Atlasi; Nazli Namazi; Mohammad Hossein Ayati (Tehran University of Medical Sciences, 2023)
As a phytochemical, berberine can modulate metabolic parameters via altering gut flora. However, findings are conflicting. In the present systematic review, we aimed to summarize the effects of berberine on gut microbiota in the models of metabolic disorders in both animal studies and clinical trials. Publications in five electronic databases including PubMed, SCOPUS, EMBASE, Web of Science, and Cochrane Library were searched systematically up to 31 May 2021 to find relevant articles with English language. Out of 4102 studies (including 2125 duplicates), 35 studies were included. In animal studies, various effects of berberine on beneficial and harmful microbiota were reported. However, findings also indicated that berberine can decrease the Firmicutes to Bacteroidetes (F/B) ratio. Three out of five studies showed positive effects of berberine on the production of short-chain fatty acids (SCFA), particularly butyrate. In three animal studies, Lipopolysacaride (LPS) concentrations decreased with berberine administration. In clinical trials (n=3) positive effects on microbiota and metabolic status were also reported. However, the quality of clinical trials was mainly low.The present systematic review showed that berberine can modulate key metabolic parameters through improving the balance of intestinal microbiome, decreasing the abundance of harmful microbiota and LPS concentrations, and increasing the production of SCFAs, particularly butyrate in animal models. However, there are limited high-quality evidence regarding the effects of berberine on gut flora in clinical trials. Although berberine can be an effective prebiotic supplement to modulate metabolic parameters, further high-quality clinical trials are needed to confirm this potential.